Post-Trial Feedback Alters Landing Performance in Adolescent Female Athletes Using a Portable Feedback System - Thomas W Kernozek (North American Sports Medicine Institute, 2021)
# Background Post-performance verbal and visual feedback based on data collected via lab-based instruments have been shown to improve landing patterns related to non-contact ACL injury. Biomechanical methods are often complex, difficult to transport and utilize in field settings, and costly, which limits their use for injury prevention. Developing systems that can readily provide feedback outside of the lab setting may support large scale use of feedback training for ACL injury prevention.